Eksplorasi potensi cagar budaya di kota Tasikmalaya sebagai pengayaan bahan ajar sejarah lokal - Fachrurozi, Miftahul Habib; Armiyati, Laely; Ramadhan, Ilham Rohman; Firdaus, Dede Wahyu (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Cultural heritage potential plays an important role in presenting meaningful history learning, unfortunately this has not been done in the Tasikmalaya city. This research aims to: 1) describe the use of cultural heritage in local history teaching materials; 2) describe a brief history of the city of Tasikmalaya, and; 3) Analyze the use of cultural heritage in the city of Tasikmalaya as enrichment of local history teaching materials. This research is qualitative research with a descriptive method where data is obtained through documentation and observation. The research results show that cultural heritage has an important role as a source of learning local history. There are 63 cultural heritage potential sites in the city of Tasikmalaya. There are a number of cultural heritage sites that can be used to enrich local historical material, including: 1) Lingga Yoni Indihiang as material to enrich local historical material during the Hindu-Buddhist era; 2) Sheikh Abdul Ghorib's grave in Kawalu during the Islamic era; 3) The Tasikmalaya Regent's official residence complex and cultural heritage in the center of Tasikmalaya city during the colonial period, and 4) the PETA Monument and the Cooperative Monument during the independence revolution. The use of the cultural heritage potentials in Tasikmalaya City in history learning can be done through two things, namely the application of the field trip method and the design of cultural heritage-based history teaching materials. This is expected to provide meaningful local history learning for students.